The Impact of Artificial Intelligence on Inclusive Education: A Systematic Review - Verónica-Alexandra Melo-López; Andrea Basantes-Andrade; Carla-Belén Gudiño-Mejía; Evelyn Hernández-Martínez (Education Sciences)
Artificial intelligence (AI) is regarded as a pivotal instrument in the realm of inclusive education, offering a means to enhance accessibility and personalize learning experiences for students with disabilities. This study presents a comprehensive and systematic review of the impact of AI on inclusive education, elucidating both its advantages and the challenges associated with its implementation. In accordance with the PRISMA guidelines, studies published between 2021 and 2024 in databases including Scopus, Web of Science, ScienceDirect, and ERIC were subjected to analysis. A bibliometric analysis was conducted using Bibliometrix to identify key trends, and ATLAS.ti was employed to organize topics such as accessibility, personalization, and ethics. The findings demonstrate that AI enhances accessibility through the provision of adapted materials, including image descriptions for visually impaired students and audio transcripts for those with hearing impairments. Furthermore, it alleviates the administrative burden on educators, enabling them to prioritize pedagogical guidance. Nevertheless, several obstacles persist, including a dearth of AI training, inadequate infrastructure, and ethical concerns regarding privacy and equitable access to technology. Ultimately, AI holds immense promise for enhancing inclusive education and fostering greater accessibility. However, its success hinges on surmounting these challenges. This study underscores the necessity for policies and strategies that ensure the ethical and sustainable utilization of AI in inclusive environments.